TEKNIK E-LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU DI KELAS VII SMP NEGERI 1 NUSA PENIDA - I Gusti Ayu Suasthi; I Wayan Arissusila; I Putu Aribawa Dana (WIDYANATYA, 2022)
ABSTRACT Learning with e-learning techniques is learning that utilizes internet technology to improve the learning environment, rich content and broad coverage. For example, SMP Negeri 1 Nusa Penida has used e-learning techniques in learning Hindu religious education, especially for grade VII students. This research was conducted to answer the problem: how is the process and implications of using e-learning techniques in learning Hindu religious education in class VII SMP Negeri 1 Nusa Penida. The purpose of this research is to increase the knowledge of students and increase the desire to learn in the classroom with the learning media Visio. This study uses data collection techniques carried out by observation, interviews, and document studies. While the theories used are constructivist and behavioristic theories. The results are: The process of using e-learning in learning Hindu religion education at SMP Negeri 1 Nusa Penida, can provide a fun and not boring learning atmosphere even though students study in their respective homes. The e-learning technique learning process aims to make it easier for students to understand the material displayed in the form of power point slides, question and answer quizzes on Google Meet, as well as to build students' learning passion so they don't feel bored when carrying out learning. Not only that, the material delivered by the teacher is acceptable, right on target and easily understood by students, despite the current Covid-19 pandemic. The implications of using e-learning techniques in learning Hindu religion education at SMP Negeri 1 Nusa Penida can be divided into three parts, namely implications for student knowledge (cognitive domain), implications for student attitudes (affective domain), and implications for psychomotor domains. ABSTRAK Pembelajaran dengan teknik e-learning merupakan pembelajaran yang memanfaatkan teknologi internet untuk meningkatkan lingkungan belajar, konten yang kaya dan cakupan yang luas. Misalnya SMP Negeri 1 Nusa Penida telah menggunakan teknik e-learning dalam pembelajaran pendidikan Agama Hindu khusunya siswa kelas VII. Penelitian ini dilaksanakan untuk menjawab permasalahan: bagaimana proses dan implikasi penggunaan teknik e-learning dalam pembelajaran pendidikan Agama Hindu di kelas VII SMP Negeri 1 Nusa Penida. Tujuan penelitian ini adalah untuk meningkatkan pengetahuan peserta didik dan meningkatkan keinginan belajar di kelas dengan media visio pembelajaran. Penelitian ini menggunakan teknik pengumpulan data dilakukan dengan obersvasi, wawancara, dan studi dokumen. Sedangkan teori yang digunakan yaitu teori konstruktivistik dan behavioristik. Hasilnya berupa: Proses penggunaan e-learning dalam pembelajaran pendidikan Agama Hindu di SMP Negeri 1 Nusa Penida, dapat memberikan suasana belajar yang menyenangkan dan tidak membosankan walaupun siswa belajar di rumahnya masing-masing. Proses pembelajaran teknik e-learning, bertujuan agar siswa lebih mudah dalam memahami materi yang ditayangkan berupa slide power point, quis tanya jawab pada Google Meet, serta membangun gairah belajar siswa agar tidak merasa bosan pada saat melaksanakan pembelajaran. Tidak hanya itu materi yang disampaikan oleh guru bisa di terima, tepat sasaran dan mudah dipahami oleh siswa, meskipun adanya pandemi Covid-19 seperti sekarang ini. Implikasi penggunaan teknik e-learning dalam pembelajaran pendidikan Agama Hindu di SMP Negeri 1 Nusa Penida dapat dibagi menjadi tiga bagian yaitu implikasi terhadap pengetahuan siswa (ranah kognitif), implikasi terhadap sikap peserta didik (ranah afektif), dan implikasi terhadap ranah psikomotor.